2008
DOI: 10.1016/j.electacta.2007.11.082
|View full text |Cite
|
Sign up to set email alerts
|

Percolation modeling investigation of TPB formation in a solid oxide fuel cell electrode–electrolyte interface

Abstract: A Monte Carlo percolation model has been developed and utilized to characterize the factors controlling triple phase boundary (TPB) formation in an SOFC electrode. The model accounts for (1) electronic conductor, ionic conductor, and gas phase percolation, (2) competition between percolation of gas and electronically conducting phases, and (3) determination of continuous, though not necessarily fully percolating, paths from TPBs to the bulk phases. The model results show that physical processes near the TPB, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 24 publications
(40 reference statements)
1
43
0
Order By: Relevance
“…The current work augments the model to simulate conductive performance measurements by development and application of a method to calculate the conductivity of an arbitrary, randomly organized conductivity network. The previous work with this model [21] has supported the understanding that the high energy conversion efficiency often attributed to fuel cell operation is critically dependent upon the morphology of the microstructure of the fuel cell electrode-electrolyte interface. It was particularly demonstrated that in this interfacial region, and within the structure of the electrode itself for composite electrodes, the necessary phases (gas, ionic conductor, and electronic conductor) form intertwining pathways and structures, with TPBs forming at the locations where these pathways all come into contact.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…The current work augments the model to simulate conductive performance measurements by development and application of a method to calculate the conductivity of an arbitrary, randomly organized conductivity network. The previous work with this model [21] has supported the understanding that the high energy conversion efficiency often attributed to fuel cell operation is critically dependent upon the morphology of the microstructure of the fuel cell electrode-electrolyte interface. It was particularly demonstrated that in this interfacial region, and within the structure of the electrode itself for composite electrodes, the necessary phases (gas, ionic conductor, and electronic conductor) form intertwining pathways and structures, with TPBs forming at the locations where these pathways all come into contact.…”
Section: Introductionmentioning
confidence: 78%
“…Not only is the number of TPBs formed important, but also location within the electrode, interconnectivity, and the length of conducting paths leading to and from each TPB are also important. The formation and location of TPBs, including their dependence upon interconnectivity of phases and interaction with the current collector geometry, have previously been investigated [21]; these observations can now be extended to the overall conductance (akin to the inverse of area specific resistance, ASR) of the electrode-electrolyte interface.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations